The micro-level dynamics of regional productivity growth: The source of divergence in Finland - Petri Böckerman; Mika Maliranta (European Regional Science Association (ERSA), 2003)
Productivity growth of the Finnish regions in 13 manufacturing industries is decomposed into micro-level sources by using plant-level data from 1975 to 1999. There are substantial regional differences in the intensity of productivity-enhancing restructuring. Dynamic competition is more intensive in Southern Finland, where the productivity level is also high. In contrast, plants located in Eastern Finland are equipped with low-productivity technologies owing to persistently sluggish micro-level dynamics. Productivity dispersion between plants within industries is greatest in Southern Finland. We argue that intensive experimentation is a more reasonable interpretation of this finding than large static X-inefficiency in this high productivity region.
Keywords: 330